The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/ep.11645
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of NO2 into aqueous (NH4)2SO3 solution in a stirred tank reactor

Abstract: Absorption experiments of NO2 from simulated flue gas into aqueous (NH4)2SO3 solution were performed in a stirred tank reactor under atmosphere pressure. As can be seen from the experimental results, the absorption rate of NO2 into (NH4)2SO3 solution increases as the (NH4)2SO3 concentration increases from 0.01 to 0.06 mol/L. As the concentration of (NH4)2SO3 solution exceeds 0.06 mol/L, the absorption process becomes gas‐film controlled. And the absorption rate increases with increasing NO2 inlet concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Effect of the Initial NO 2 Concentration on NO 2 Absorption by Na 2 SO 3 and Na 2 SO 3 /NaHSO 3 . As shown in Figure 7, increasing the initial concentration of NO 2 increased the NO x absorption efficiency from 95.4% to 97.8% in the Na 2 SO 3 absorption system and from 96.0% to 97.8% in the Na 2 SO 3 /NaHSO 3 absorption system, and these results are compatible with the results of Guo et al 21 As explained above, the absorption process was mainly controlled by the gas film when the S(IV) concentration exceeded 0.2 mol/L (Figure ). In addition, the gas-phase driving force increased as the initial NO 2 concentration increased, and a high initial NO 2 concentration enhanced the amount of NO 2 dissolved in the liquid phase, which promoted the rates of reactions 6−9.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Effect of the Initial NO 2 Concentration on NO 2 Absorption by Na 2 SO 3 and Na 2 SO 3 /NaHSO 3 . As shown in Figure 7, increasing the initial concentration of NO 2 increased the NO x absorption efficiency from 95.4% to 97.8% in the Na 2 SO 3 absorption system and from 96.0% to 97.8% in the Na 2 SO 3 /NaHSO 3 absorption system, and these results are compatible with the results of Guo et al 21 As explained above, the absorption process was mainly controlled by the gas film when the S(IV) concentration exceeded 0.2 mol/L (Figure ). In addition, the gas-phase driving force increased as the initial NO 2 concentration increased, and a high initial NO 2 concentration enhanced the amount of NO 2 dissolved in the liquid phase, which promoted the rates of reactions 6−9.…”
supporting
confidence: 90%
“…Although the NO 2 absorption performance by sulfite is good, the main N-containing products from the absorption of NO 2 in solution are nitrate and nitrite. ,, Nitrate can induce the fertilization of seawater and reduce the dissolved oxygen content in seawater, hence affecting biodiversity. According to the Marine Environment Protection Committee (MEPC), the nitrate concentration in scrubber water should not exceed 60 mg/L. Moreover, nitrite is extremely unstable and easily oxidized to nitrate.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In light of the difficulty in coupling discrete SO 2 and NO x removal approaches, developing an effective technology for simultaneous removal of SO 2 and NO x is a desired goal. Various technologies have been developed for simultaneous removal of SO 2 and NO x , such as solid-phase absorption, 15,16 nonthermal plasma, 17,18 enhanced wet scrubbing, 7,19,20 etc. WFGD can be used for the combined removal of NO x and SO 2 provided that the NO x is in a highly oxidized state with high water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Scrubbing tests conducted in previous studies revealed that sodium sulfite (Na 2 SO 3 ) can effectively reduce aqueous NO 2 in scrubbing liquor and promote the absorption of NO 2 from the influent gas . These studies used pure NO or NO 2 in air streams and alkaline Na 2 SO 3 solution as the scrubbing liquor.…”
Section: Resultsmentioning
confidence: 99%